(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the antibacterial efficacy of the novel compound 4-(2-hydroxypropan-2-yl)cyclohex-1-en-1-ol compared to the standard antibiotic ampicillin. The Calotropis procera root extract was prepared with using different solvents and thin layer chromatography (TLC) was used for isolation and 1H NMR, 13C NMR, Mass spectral studies are used for characterization of isolated compound for subsequent antibacterial testing. Using standard agar diffusion methods, the compound was tested for antibacterial activity against Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, and Escherichia coli. The zone of inhibition values for the novel compound were 4 mm against Staphylococcus aureus, 4 mm against Escherichia coli, and 5 mm against Pseudomonas aeruginosa, indicating superior antibacterial activity compared to ampicillin. Given the rising antibiotic resistance, the effectiveness of 4-(2-hydroxypropan-2-yl)cyclohex-1-en-1-ol against these pathogens underscores its potential as a therapeutic candidate. Further studies are necessary to elucidate its mechanism of action, pharmacokinetics, and in vivo efficacy, which will be crucial for evaluating its suitability in clinical applications. Overall, this research contributes to the ongoing search for new antibacterial agents capable of combating resistant bacterial strains, emphasizing the need for continued exploration of novel compounds in the fight against infectious diseases.